2004
DOI: 10.1111/j.1745-4573.2004.tb00685.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF FEEDING ELEVATED LEVELS OF VITAMINS D3 AND E ON BEEF QUALITY

Abstract: Yearling (12 Angus, 12 Wagyu≥Angus) and 2‐year old heifers (12 Angus, 12 Wagyu≥Angus) were fed elevated levels of Vitamin D3and/or Vitamin E to evaluate beef quality. Warner‐Bratzler shear force (WBS) and sensory characteristics were determined on steaks from the Longissimus lumborum (LL) aged 21 days and on steaks from the Gluteus medius (GM) and Psoas major (PM) aged 7 days. Steaks were cut from all muscles, displayed for 5 days then L*value and hue angle were determined. Vitamin E supplemented heifers recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
1
4
0
6
Order By: Relevance
“…In this study, D 3 was not effective in improving meat tenderness, which responded more markedly to aging time. These results are similar to those found by Scanga et al (2001), Rentfrow et al (2001) Table 2 -Least squares means, overall mean, coefficient of variation and significance of concentrations of muscle minerals in Bos indicus animals supplemented with vitamin D 3 for 10 consecutive days prior to slaughter.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, D 3 was not effective in improving meat tenderness, which responded more markedly to aging time. These results are similar to those found by Scanga et al (2001), Rentfrow et al (2001) Table 2 -Least squares means, overall mean, coefficient of variation and significance of concentrations of muscle minerals in Bos indicus animals supplemented with vitamin D 3 for 10 consecutive days prior to slaughter.…”
Section: Resultssupporting
confidence: 86%
“…No differences (P > 0.05) were found among D 3 supplementation levels for plasma concentrations of calcium, sodium, potassium and magnesium (Table 1). These results contradict those presented by Karges et al (2001), Kotrla et al (2001), Scanga et al (2001), Rentfrow et al (2001), Berry et al (2000), Enright et al (2000a;, Morgan & Gill (2000), and Rider et al (2000), who reported increased plasma calcium concentration in response to D 3 . In a study by Swanek (1999a;, the concentration of plasma calcium increased between 8 and 48% as a result of D 3 supplementation, mainly because of the effect of the vitamin on calcium metabolism, increasing intestinal reabsorption and calcium loss from bone deposits.…”
Section: Resultsmentioning
confidence: 61%
“…Essa pode ser uma das razões pelas quais o efeito da suplementação com vitaminas foi nulo. Rentfrow et al (2001) alimentaram novilhas com suplementação de altos níveis de vitamina D 3 , ou com mistura de vitamina D 3 e vitamina E, e reportaram elevação do cálcio sérico, sem que tenha havido alteração ou redução na força de cisalhamento. Montgomery et al (2004b) trabalharam com novilhos tratados com 5x10 6 UI de vitamina D 3 , pelo período de oito dias antes do abate, e relataram melhora na maciez da carne maturada por sete dias, por meio da avaliação da força de cisalhamento entre animais que receberam suplemento e o grupo controle.…”
Section: Resultsunclassified
“…Initially, they evaluated fresh and irradiated raw beef. They were then familiarized with the sensory attributes of beef provided with terminology (Rentfrow et al. 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Initially, they evaluated fresh and irradiated raw beef. They were then familiarized with the sensory attributes of beef provided with terminology (Rentfrow et al 2004). They developed a set of descriptive parameters for odor via open discussion with the guidance of a panel leader to establish agreement on characteristics as described by Rojas and Brewer (2008).…”
Section: Odor Evaluationmentioning
confidence: 99%